2016
DOI: 10.1097/md.0000000000005683
|View full text |Cite
|
Sign up to set email alerts
|

Active case finding strategy for chronic obstructive pulmonary disease with handheld spirometry

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…While screening for COPD in asymptomatic adults is not recommended,7 active case-finding strategies should be considered for early diagnosis of COPD in high-risk subjects 811. Although smoking is the most commonly encountered risk factor for COPD,1 COPD awareness among smokers is low in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…While screening for COPD in asymptomatic adults is not recommended,7 active case-finding strategies should be considered for early diagnosis of COPD in high-risk subjects 811. Although smoking is the most commonly encountered risk factor for COPD,1 COPD awareness among smokers is low in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Research ERF in patients with COPD is optional and allows to objectify the degree of airflow obstruction, reversibility and its variability, and the effectiveness of treatment and physical rehabilitation carried out (Borges, 2014;Deepak, 2014; Global Strategy for the Diagnosis, Management and Prevention of Chronic Obstructive Pulmonary Disease, GOLD Executive Summary, 2017; Kim, 2016).…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 18 Moreover, a recent publication showed that the added value of a screening questionnaire next to microspirometry is low. 14 …”
Section: Discussionmentioning
confidence: 99%